Interactions Between Alternative Therapies and Mental Health Services in Public Hospitals of Argentina - Saizar, María Mercedes (2012)
In this article we describe the phenomenon of therapeutic complementarity between alternatives therapies and biomedicine in Public Hospitals of Buenos Aires [Argentina]. We contextualize the phenomenon in a global and local field. Features specific to Argentina make this phenomenon interesting. The first of these is that biomedicine is the only type of medicine that is legally authorized to act on the body; nevertheless, alternative practices have flourished not only in the private health sector but also in the Public Hospitals run by the State. A second feature refers to the alternative practices in the Mental Health area that brings about a singular interaction between two different therapeutic models. Based on a qualitative study in public hospitals, we look into the reasons that generate the phenomenon, underlining the forms in which it expresses itself and the complexity of a field under construction that implies the resignification of the concepts related to health and disease.